THE INFLUENCE OF BRAND IDENTITY AND INSTAGRAM SOCIAL MEDIA MARKETING ON CUSTOMER LOYALTY AT UNO UNO COFFEE AND RESTO - Alfian Zulfaizar; Moch Arfani; Liling Listyawati (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study evaluates the impact of Brand Identity and Instagram Social Media Marketing on Customer Loyalty at Uno Uno Coffee and Resto Jakarta, both separately and together. Although brand identity and social media marketing have each been examined as separate predictors of loyalty, limited empirical attention has been paid to their combined effect within Indonesia’s local coffee shop sector—a gap this study addresses by testing both determinants concurrently in an emerging urban food-and-beverage context. A quantitative method with a causal descriptive design was applied, relying on a sample of 96 respondents taken via a purposive sampling technique based on the Cochran formula calculation. The sample criteria included active consumers who are followers of the company’s Instagram with a transaction history of at least two times in the last quarter. The instrument in the form of a Likert scale questionnaire (1–5) was processed using multiple linear regression via SPSS, where all data were proven valid, reliable, and passed the classical assumption test (normality and freedom from multicollinearity). The results of the analysis showed that Brand Identity had a significant positive partial effect on Customer Loyalty, whereas Instagram Social Media Marketing did not show a significant partial contribution. Nevertheless, the two variables were proven to exert a significant simultaneous effect on Customer Loyalty. These findings confirm that strengthening brand identity is a key driver of consumer loyalty to local coffee shops, while marketing strategies via Instagram still require content reorientation for optimal impact. This study contributes theoretically by clarifying the relative weight of brand identity versus Instagram-based marketing activities in loyalty formation, and offers practical guidance for coffee shop managers on prioritizing brand-identity consistency alongside Instagram content strategy.